Identifying Isolated Systolic Hypertension From Upper-Arm Cuff Blood Pressure Compared With Invasive Measurements - Picone, Dean S.; Schultz, Martin G.; Armstrong, Matthew K.; Black, J. Andrew; Bos, Willem Jan W.; Chen, Chen Huan; Cheng, Hao Min; Cremer, Antoine; Dwyer, Nathan; Hughes, Alun D.; Kim, Hack Lyoung; Lacy, Peter S.; et al. (Hypertension, 2021)
Isolated systolic hypertension (ISH) is the most common form of hypertension and is highly prevalent in older people. We recently showed differences between upper-arm cuff and invasive blood pressure (BP) become greater with increasing age, which could influence correct identification of ISH. This study sought to determine the difference between identification of ISH by cuff BP compared with invasive BP. Cuff BP and invasive aortic BP were measured in 1695 subjects (median 64 years, interquartile range [55-72], 68% male) from the INSPECT (Invasive Blood Pressure Consortium) database. Data were recorded during coronary angiography among 29 studies, using 21 different cuff BP devices. ISH was defined as ≥130/<80 mm Hg using cuff BP compared with invasive aortic BP as the reference. The prevalence of ISH was 24% (n=407) according to cuff BP but 38% (n=642) according to invasive aortic BP. There was fair agreement (Cohen κ, 0.36) and 72% concordance between cuff and invasive aortic BP for identifying ISH. Among the 28% of subjects (n=471) with misclassification of ISH status by cuff BP, 20% (n=96) of the difference was due to lower cuff systolic BP compared with invasive aortic systolic BP (mean, -16.4 mm Hg [95% CI, -18.7 to -14.1]), whereas 49% (n=231) was from higher cuff diastolic BP compared with invasive aortic diastolic BP (+14.2 mm Hg [95% CI, 11.5-16.9]). In conclusion, compared with invasive BP, cuff BP fails to identify ISH in a sizeable portion of older people and demonstrates the need to improve cuff BP measurements.
CRIS-Team Scopus Importer:2021-02-05
Keywords: aorta; blood pressure; coronary angiography; hypertension; prevalence